Motivations of New Zealand triathletes : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Watson, Jenny, M.A. (Massey University, 1996)
The studying of motivation in the sporting environment has been seen by researchers as important for reasons such as development of theories and models of motivation in sport as well as improving coaching and training techniques though better understanding of athletes' motivations. The present study aimed to examine the motivations of triathletes selected for the New Zealand team for their age group. Other objectives of the study were to compare motivations of males and females, to examine the reliability of the Sport Orientation Questionnaire (Gill & Deeter, 1988), and to examine the effects of training related variables on SOQ scores in order to expand on the nature of sport orientations. Thirty-five male and female triathletes, aged from 18 to 66 years, who had been selected as part of the national Triathlon team in their age group section, participated in the study. Participants completed self-administered questionnaires developed by the researcher as well as the Sport Orientation Questionnaire (Gill & Deeter, 1988). Four of the participants were also interviewed. Results showed that the triathletes in the sample were highly motivated and had high levels of enjoyment. They reported a number of different factors which motivated them to participate and compete in Triathlon. Although no significant gender differences were found on the three subscales of the SOQ, qualitative data were contradictory. Statistical analysis provided further support for the continued use of the SOQ as a multi-dimensional measure of sport orientations. However, it was suggested that factors which lead to a feeling of success should be examined separately from other motivating factors.
Keywords: Psychological aspects; Triathlon; Athletes; Motivation Psychology